Concurrent Training and Interindividual Response in Women with a High Number of Metabolic Syndrome Risk Factors - Herrera-Valenzuela, T (Frontiers Media S.A., 2022)
The non-responders (NRs) after exercise training have been poorly studied in populations with morbid obesity. The purpose of this study was to determine the NR prevalence after 20 weeks of concurrent training of morbidly obese women with a high or low number of metabolic syndrome (MetS) risk factors. Twenty-eight women with morbid obesity participated in an exercise training intervention and were allocated into two groups distributed based on a high (≥3, n = 11) or low number (<3, n = 17) of MetS risk factors. The main outcomes were waist circumference (WC), fasting plasma glucose (FPG), high-density lipids (HDL-c), triglycerides (Tg), and systolic (SBP) and diastolic (DBP) blood pressure, and secondary outcomes were body composition, anthropometric and physical fitness, determined before and after 20 weeks of concurrent training. NRs were defined as previously used technical error cut-off points for the MetS outcomes. Significantly different (all p < 0.05) prevalences of NRs between the H-MetS vs. L-MetS groups (respectively) in WC (NRs 18.2 % vs. 41.1 %, p < 0.0001), SBP (NRs 72.7 % vs. 47.0 %, p = 0.022), DBP (NRs 54.5 % vs. 76.4 %, p < 0.0001), FPG (NRs 100% vs. 64.8 %, p < 0.0001), and HDL-c (NRs 90.9 % vs. 64.7 %, p = 0.012) were observed. In addition, the H-MetS group evidenced significant changes on ΔSBP (−10.2 ± 11.4 mmHg), ΔFPG (−5.8 ± 8.2 mg/dl), ΔHDL-c (+4.0 ± 5.9 mg/dl), and ΔTg (−8.8 ± 33.8 mg/dl), all p < 0.05. The L-MetS group only showed significant changes in ΔWC (−3.8 ± 5.0 cm, p = 0.009). Comparing H-MetS vs. L-MetS groups, significant differences were observed in ∆FPG (−5.8 ± 8.2 vs. +0.3 ± 3.2 mg/dl, p = 0.027), but not in other MetS outcomes. In conclusion, 20 weeks of concurrent training promotes greater beneficial effects in morbidly obese patients with a high number of MetS risk factors. However, the NR prevalence for improving MetS outcomes was significantly superior in these more-diseased groups in SBP, FPG, and HDL-c, independent of their major training-induced effects. Copyright © 2022 Delgado-Floody, Chirosa-Ríos, Caamaño-Navarrete, Valdés-Badilla, Herrera-Valenzuela, Monsalves-Álvarez, Núñez-Espinosa, Castro-Sepulveda, Guzmán-Muñoz, Andrade and Álvarez.
Keywords: morbid obesity; physical activity; exercise; sleep quality; quality of life